The quality of the new birth certificate data: a validation study in North Carolina. - Buescher, P A (1993)
A random sample of 395 December 1989 North Carolina birth certificates and the corresponding maternal hospital medical records were examined to validate selected items. Reporting was very accurate for birth-weight, Apgar score, and method of delivery; fair to good for tobacco use, prenatal care, weight gain during pregnancy, obstetrical procedures, and events of labor and delivery; and poor for medical history and alcohol use. This study suggests that many of the new birth certificate items will support valid aggregate analyses for maternal and child health research and evaluation.